1989
DOI: 10.1007/bf01911681
|View full text |Cite
|
Sign up to set email alerts
|

A thermal analysis study of the combustion characteristics of Victorian brown coals

Abstract: Simultaneous TG, DTA techniques have been applied to investigate the combustion characteristics of Victorian brown coal derived from different coal fields and including various l!thotypes. TG and DTA profiles of the entire combustion process were obtained to provide a set ofpardmeters which characterize the oxidation potential of these coal samples. These parameters can also be used to predict the combustion performance of pulverized coal in industrial furnaces. The area of the major DTA combustion peak is clo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

1989
1989
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 6 publications
(7 reference statements)
0
10
0
Order By: Relevance
“…Studies on the thermal analysis of Victorian brown coal to determine pyrolysis and combustion kinetics can be found in the open literature [14][15][16][17][18][19]. However, very few studies reported provided information on the gasification kinetics of Victorian brown coals; those available were summarised by Bhattacharya et al [20].…”
Section: Introductionmentioning
confidence: 99%
“…Studies on the thermal analysis of Victorian brown coal to determine pyrolysis and combustion kinetics can be found in the open literature [14][15][16][17][18][19]. However, very few studies reported provided information on the gasification kinetics of Victorian brown coals; those available were summarised by Bhattacharya et al [20].…”
Section: Introductionmentioning
confidence: 99%
“…The first and second DTA peaks appearing at around 60°C (endothermic) and 285°C are due to the vaporization of moisture and combustion of volatile matter, respectively [12]. However, the third peak (exothermic) is at 460°C to 509°C representing the combustion of char [9]. Table 1 shows the effect of temperature on combustion parameters based on the DTA-TG analysis.…”
Section: Products Properties: Tg-dta Examination Resultsmentioning
confidence: 99%
“…4. From the DTA-TG curves, a number of combustion parameters can be derived, such as, ignition temperature (T ig ), maximum combustion rate temperature (T max ), maximum combustion rate (R max ) and char burn-out temperature (T bo ) [9][10][11]. Ignition temperature (T ig ) is an important characteristic of peat fuel combustion, especially for raw peat due to its high intensity of spontaneous combustion [4].…”
Section: Products Properties: Tg-dta Examination Resultsmentioning
confidence: 99%
“…The decreases of differential temperature at the first DTA peak for the raw coal corresponds to the consumption of heat for the removal of moisture. The second peak relates to the heat released and the heat consumption as a result of the decomposition, the poly condensation of pyrolysis product and the combustion of volatile matter [10]. A hydrogen bond is disrupted during the upgrading and takes place in the low rank coal.…”
Section: Characterization Of Upgraded Brown Coal 39mentioning
confidence: 99%